203k views
3 votes
Finding Derivatives Implicity In Exercise,Find dy/dx implicity.
x2y - ey - 4 = 0

User Jgerman
by
5.6k points

1 Answer

5 votes

Answer:


(dy)/(dx) = (2xy)/(e^y-x^2)

Explanation:

We are given the following in the question:


x^2y - e^y - 4 = 0

We have to find the derivative of the given expression implicitly.

Formula:


\text{Product rule:}\\\\(d(a.b))/(dx) = b(da)/(dx) + a(db)/(dx)\\\\(d(x^n))/(dx) = nx^(n-1)\\\\\frac{d(\text{Constant})}{dx} = 0

The derivation takes place in the following manner:


x^2y - e^y - 4 = 0\\\text{Differentiating both sides we get,}\\(x^2dy + 2xdxy)-e^ydy = 0\\(x^2-e^y)dy + (2xy)dx = 0\\(x^2-e^y)dy = - (2xy)dx\\\\(dy)/(dx) = (-2xy)/(x^2-e^y)

Thus, the implicit differential is given by:


(dy)/(dx) = (2xy)/(e^y-x^2)

User Henrikmerlander
by
5.3k points